The Future Of Blog In The Efl Writing Classroom - Mariani, Mariani; Hanna, Hanna; Sartiah, Sartiah (Journal of Language Education and Educational Technology (JLEET), 2016)
Little investigation has been conducted in the field of English as a Foreign Language (EFL) regarding writing experiences through blogs. Drawing upon Vygotskyâ€™s constructivist theory in language learning, this study was set out to investigate the effect utilizing web blog as a teaching media on studentsâ€™ writing competence. Thirty-one fourth semester students of English Literature study program in the Faculty of Cultural Studies, Halu Oleo University who took Creative Writing subject in the academic year 2015/2016 participated in the research. Data of this research were obtained from studentsâ€™ results of pre- and post-test, as well as pre-post in-depth interview which was conducted to find out studentsâ€™ perception towards the use of web blogs in their learning. The research analyzed both quantitative and qualitative data, the former to investigate the extent to which the use of web blog has been effective, and the latter to gauge studentsâ€™ perceptions of the teaching media under investigation. Two research questions were posed: (1) Is there any significant effect of utilizing web blog on the studentsâ€™ competence in writing narrative essay? (2) How do studentsâ€™ perceptions of using blogs influence their experiences in their English writing?. The researcher run a paired sample t-test with 2 tailed t-test using the SPSS 16 to test proposed hypothesis. To reveal studentsâ€™ perception, descriptive data were transformed into words. Analysis of the data obtained resulted in the followings: pre-test score (M=76.38; SD = 8.77), post-test score (M=86.29; SD=7.78), Df= 30, t-table = 1,697 and t-test = 10.686. Result of paired sample t-test showed that t-test â‰¥ t-table at sig Î± â‰¤ 0.05 orÂ  Hâ‚€ was rejected and Hâ‚ was accepted. These results indicated a significant different on studentsâ€™ writing competence before and after treatment. It can therefore be concluded that utilizing web blog as media for teaching writing is effective not only in improving studentâ€™s writing competence, but also in creating positive learning environment